2020
DOI: 10.1111/tid.13471
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin for treating tuberculosis in solid organ transplant recipients: A retrospective observational study and literature review

Abstract: Background The treatment of tuberculosis (TB) in solid organ transplant (SOT) recipients is challenging owing to interactions between rifampin and immunosuppressive drugs. Rifabutin, a rifamycin with excellent activity against Mycobacterium tuberculosis and that induces cytochrome p450 less, may facilitate treatment. We report our experience with rifabutin for treating TB in SOT recipients and review the available literature. Methods A retrospective observational study of all SOT recipients with TB between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Multiple studies have demonstrated that the development of posttransplant TB is associated with significant mortality [8 ▪ ,9–11,13,51,53,54 ▪▪ ,55,56], graft rejection or graft failure [9,10,12,13,55–58]. A recent systematic review and meta-analysis estimated the prevalence of TB disease in SOT at 3%; however, these estimates were mostly from middle to high-incidence countries [3 ▪ ].…”
Section: Management Of Tuberculosis Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated that the development of posttransplant TB is associated with significant mortality [8 ▪ ,9–11,13,51,53,54 ▪▪ ,55,56], graft rejection or graft failure [9,10,12,13,55–58]. A recent systematic review and meta-analysis estimated the prevalence of TB disease in SOT at 3%; however, these estimates were mostly from middle to high-incidence countries [3 ▪ ].…”
Section: Management Of Tuberculosis Diseasementioning
confidence: 99%
“…Posttransplant TB can present with fever alone mandating a high clinical suspicion, particularly in those with risk factors [11,13,53,56,58,59]. Pulmonary TB (PTB) is generally common (47–87%), followed by extrapulmonary TB (EPTB) (11–41%), disseminated (2–23%), and miliary TB (2–8%) [3 ▪ ,8 ▪ ,9,10,13,53,54 ▪▪ ,56,57]. However, EPTB and disseminated TB were observed in 85% and 66%, respectively, in a single-center study [11].…”
Section: Management Of Tuberculosis Diseasementioning
confidence: 99%
“…36,37 To address the concern of rifampin use after transplant, rifabutin has been substituted to treat active TB following SOT with success. 38,39 Nontuberculous mycobacteria…”
Section: Active Tuberculosis-when To Transplant and Posttransplant Outcomesmentioning
confidence: 99%
“…Therefore, a rifampin‐sparing regimen has been attempted in SOT recipients to avoid this risk of lower bioavailability of an immunosuppressive agent 16,17 . Alternatively, rifabutin can be chosen as a reliable substitute to rifampin in these patients, 18,19 considering that rifabutin has comparable potent activity against M. tuberculosis with rifampin, 20 although rifabutin is a less potent inducer of the cytochrome P450 3A4 microsomal enzyme 21–23 …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Therefore, a rifampin-sparing regimen has been attempted in SOT recipients to avoid this risk of lower bioavailability of an immunosuppressive agent. 16,17 Alternatively, rifabutin can be chosen as a reliable substitute to rifampin in these patients, 18,19 considering that rifabutin has comparable potent activity against M. tuberculosis with rifampin, 20 although rifabutin is a less potent inducer of the cytochrome P450 3A4 microsomal enzyme. [21][22][23] However, as previous studies on the clinical experience of the use of rifabutin in SOT recipients have been limited, little is known about the change in the drug level and need for dose adjustment of calcineurin inhibitor when calcineurin inhibitor used with rifabutin.…”
Section: Introductionmentioning
confidence: 99%